Predictors of Failure of Closure in Percutaneous EVAR Using the Prostar XL Percutaneous Vascular Surgery Device. Issue 1 (January 2015) - Rijkée, M.P.; Statius van Eps, R.G.; Wever, J.J.; van Overhagen, H.; van Dijk, L.C.; Knippenberg, B.
<x xml:space="preserve">Abstract</x> Objective To identify predictors of failure in percutaneous endovascular aneurysm repair (P-EVAR) using the Prostar XL Percutaneous Vascular Surgery Device (Abbot Vascular, Santa Clara, CA, USA) and the need for conversion to conventional femoral cutdown (O-EVAR). Methods Consecutive patients who underwent P-EVAR with the Prostar XL device between January 2009 and April 2012 were included in this series. Patients with a circular calcified common femoral artery (CFA) on computed tomography angiography were operated using O-EVAR and were therefore excluded. To identify predictors of success of closure in P-EVAR, artery characteristics, sheath size used, and comorbidities were analyzed in a univariate logistic regression model. Results Percutaneous access was achieved in 154 femoral access sites with conversion to O-EVAR was needed in 10 (6.5%). Significant predictors of conversion included sheath size (continuous, relative risk [RR] 1.50, p < .03) and the ratio between sheath size and CFA diameter >0.75 (RR 8.93, p < .01). Variables such as calcification quantity scores, CFA diameter, body mass index, and comorbidities were not significant. Conclusion The data demonstrate that sheath size, in particular, combined with CFA diameter predicts failure of closure in P-EVAR using the Prostar XL device. This ratio can be utilized to help in decision making with regard to the EVAR approach. A ratio of >0.75 would favor a primary open groin approach.